2019
DOI: 10.2174/1874149501913010260
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Strength of Modified Reactive Powder Concrete One Way Slabs

Abstract: Background: Over the last three decades, the interest in using advanced high-performance materials in the construction industry has been increasing worldwide. Recently, a very high strength cement-based composite with high ductility called Reactive Powder Concrete (RPC) has been developed. The RPC concept is based on the principle that a material with a minimum of defects such as micro-cracks and voids will be able to achieve greater load-carrying capacity and durability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The saving of concrete in bubble slabs was 18% compared to the solid slab, and the bubble slabs achieve the requirements of sustainability [22]. Abtan and Hassan (2019) studied the flexural strength of modified reinforced reactive powder concrete (MRPC) one-way slabs, the result showed that: An improvement in the ultimate load was achieved for modified reactive powder concrete slabs when increasing the thickness of the slab, adding the steel fibers with a proportion of (0.4%, 0.8%) to the concrete mixture of the MRPC slabs enhanced the ultimate load capacity, increased the ductility of MRPC slabs, improved their stiffness, reduced the rate of propagation of cracks, and reduces the width of cracks [23]. From the previous studies which dealt with the field of the structural behavior of reactive powder reinforced concrete one-way slab, it can be noted that most of these studies focused on investigating the effect of opening in RPC one-way slabs, sustainable flooring elements of RPC bubbled slabs, modified reactive powder concrete one-way slabs, and some other parameters, but did not focus on the behavior of RPC one-way solid slabs, which is one of the fields that require study because, until this time, no research has dealt with this field and there is a lack of information about the analysis and design of RPC one-way solid slabs.…”
Section: Introductionmentioning
confidence: 98%
“…The saving of concrete in bubble slabs was 18% compared to the solid slab, and the bubble slabs achieve the requirements of sustainability [22]. Abtan and Hassan (2019) studied the flexural strength of modified reinforced reactive powder concrete (MRPC) one-way slabs, the result showed that: An improvement in the ultimate load was achieved for modified reactive powder concrete slabs when increasing the thickness of the slab, adding the steel fibers with a proportion of (0.4%, 0.8%) to the concrete mixture of the MRPC slabs enhanced the ultimate load capacity, increased the ductility of MRPC slabs, improved their stiffness, reduced the rate of propagation of cracks, and reduces the width of cracks [23]. From the previous studies which dealt with the field of the structural behavior of reactive powder reinforced concrete one-way slab, it can be noted that most of these studies focused on investigating the effect of opening in RPC one-way slabs, sustainable flooring elements of RPC bubbled slabs, modified reactive powder concrete one-way slabs, and some other parameters, but did not focus on the behavior of RPC one-way solid slabs, which is one of the fields that require study because, until this time, no research has dealt with this field and there is a lack of information about the analysis and design of RPC one-way solid slabs.…”
Section: Introductionmentioning
confidence: 98%